Distinct bacterial community structures and arsenic biotransformation gene profiles in dust - Yin, Yi; Lin, Yu-Ting; Hu, Gong-Ren; Yu, Rui-Lian; Sun, Xiao-Hui; Yan, Yu (Frontiers in Microbiology, 2025)
IntroductionMicroorganisms, which are ubiquitous in the environment, have evolved a diverse array of arsenic biotransformation genes (ABGs). Dust harbors a wide range of microorganisms. However, the distinct characteristics of bacterial community structures and ABG profiles in dust, compared with those in other environments such as soil and water, remain poorly understood.MethodsIn this study, dust samples were simultaneously collected alongside surrounding soil and seawater samples in Xiamen, a coastal city of China, to investigate the distinct profiles and potential sources of bacterial communities and ABGs in dust using 16S rRNA gene amplicon sequencing and metagenomic sequencing.Results and discussionAbundant and diverse bacterial communities and ABGs were detected in dust, revealing significant differences in community structures and ABG profiles compared with those in soil and seawater. Soil was identified as the primary source for both bacterial communities and ABGs in dust through fast expectation–maximization microbial source tracking (FEAST). Acetobacteraceae, which showed significantly greater relative abundance (p < 0.001) in dust than in soil and seawater, was also identified as a keystone taxon in the dust bacterial co-occurrence network. Furthermore, metagenome-assembled genomes (MAGs) affiliated with Acetobacteraceae were effectively recovered from dust via metagenomic binning, and these MAGs harbored an array of ABGs, indicating that Acetobacteraceae could be important hosts for ABGs in dust. Overall, our findings offer new insights into bacterial communities and ABGs in dust, thereby improving our understanding of arsenic biogeochemical cycling.